2019
DOI: 10.2320/matertrans.mt-maw2019005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Vanadium Species on the Hydrogen Permeability through Vanadium Membrane without Palladium-Catalyst Overlayer

Abstract: The effects of surface V species on the hydrogen permeability through V membrane without Pd-catalyst overlayer are investigated by the hydrogen permeation test at 773 K and the XPS measurement. The steady-state hydrogen permeation flux through Pd-coating free V membrane after the redox treatment is more than twice that of the non-treated membrane. The hydrogen flux after 50 hours, however, are almost the same regardless of the redox treatment since the redox-treated membrane is deactivated during the hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…29) In addition, Shirasu et al reported that the multi-valence state of transition metals was important for the catalytic effects of the reaction with H 2 in the case of the vanadium membrane. 30) Based on the analogy of this report, it is possible that the balance of the existing Nb valence states is effective for obtaining a highly active state as the catalyst. It is evident from the above-stated results that reduction states are important for obtaining high catalysis on Nb oxide for the hydrogen absorption and desorption reaction of Mg.…”
Section: Resultsmentioning
confidence: 94%
“…29) In addition, Shirasu et al reported that the multi-valence state of transition metals was important for the catalytic effects of the reaction with H 2 in the case of the vanadium membrane. 30) Based on the analogy of this report, it is possible that the balance of the existing Nb valence states is effective for obtaining a highly active state as the catalyst. It is evident from the above-stated results that reduction states are important for obtaining high catalysis on Nb oxide for the hydrogen absorption and desorption reaction of Mg.…”
Section: Resultsmentioning
confidence: 94%